Antimicrobial efficacy of Novel Ethanolic Extract of Morinda Citrifolia Against Enterococcus Feacalis by Agar Well Diffusion Method and Minimal Inhibitory Concentration- An Invitro Study. - Gummuluri, Sriram; Kavalipurapu, Venkata Teja; Kaligotla, Apoorva Vasundhara (Brazilian Dental Science, 2019)
Introduction: the long term success of root canal treatment is ultimately related to the effective debridement and disinfection of the root canal system. Hence, the irrigants play an important role in achieving the good penetrability and bactericidal activity. The present study was mainly aimed at evaluating the invitro antimicrobial efficacy of Novel Ethanolic Extract of Morinda Citrifolia by agar well diffusion and minimal inhibitory concentration. Materials and Methods:the antimicrobial efficacy of the Novel Ethanolic Extract of Morinda Citrifolia was tested using agar well diffusion and minimal inhibitory concentration was assessed. The zone of inhibitions were determined at 10 mg/ml concentration of Ethanolic Extract of Morinda Citrifolia on agar well plate and Minimal Inhibitory Concentration (MIC) against tested microorganism. Results: results obtained in the present study by both qualitative and quantitative experiments revieled that the tested Ethanolic Extract of Morinda Citrifolia possesses potential antibacterial activity against Enterococcus Feacalis when compared with standard antibiotic tetracycline. the highest zone of inhibition of 15mm was showed at 1000micrograms by agar well diffusion assay. The optimal antimicrobial activity was seen at 250micrograms for Morinda Citrifolia against Enterococcus Feacalis.Conclusion: novel Ethanolic extract of Morinda Citrifolia has shown an optimal antimicrobial activity against E.Feaclais. But still, future studies are still needed.